Efficacy and tolerability of methylprednisolone pulse therapy in childhood epilepsies other than infantile spasms - Bast, Thomas; Rating, Dietz; Schubert-Bast, Susanne (Neuropediatrics, 2014)
This retrospective study included 54 children with epilepsy. The treatment consisted of four pulses with single doses of 20 mg/kg/d methylprednisolone (MPR), administered every week on 3 consecutive days. After this initial phase, the intervals between the pulses were increased based on individual factors. MPR pulses were administered exclusively orally in 39 patients and 7.8% of all pulses were applied intravenously. After four pulses, 30 of 54 (56%) patients were responders, according to several clinical and electroencephalography criteria. A response was obtained in 12 of 20 (60%) cases with genetic, 7 of 17 (41%) with structural metabolic, and 11 of 17 (65%) with unknown etiology. Responder rates were 11 of 15 (73%) in patients with continuous spike-waves in slow sleep (CSWS) or Landau-Kleffner syndrome, 2 of 6 in patients with myoclonic astatic epilepsy or Lennox-Gastaut syndrome, and 17 of 31 (55%) in patients with unclassified epilepsies. A response was not correlated with any epilepsy-related clinical factor. The patients received a median of eight MPR pulses (range, 1-52), and the median duration of the therapy was 11 weeks. The response was maintained in 19 of 30 (63%) patients, and 3 of 24 (13%) without initial response became seizure-free (total responder rate at the end of the therapy 22/54 [41%]). The majority of patients experienced adverse effects that were typically mild and transient.